2020
DOI: 10.1186/s13068-020-1656-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of bicarbonate transporters in the marine cyanobacterium Synechococcus sp. PCC 7002 increases growth rate and glycogen accumulation

Abstract: Background: Synechococcus sp. PCC 7002 is an attractive organism as a feedstock and for photoautotrophic production of biofuels and biochemicals due to its fast growth and ability to grow in marine/brackish medium. Previous studies suggest that the growth of this organism is limited by the HCO 3 − transport across the cytoplasmic membrane. Tools for genetic engineering are well established for this cyanobacterium, which makes it possible to overexpress genes of interest. Results: In this work, we overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…SbtA is a high-affinity, low flux, inducible sodium (Na +) dependent HCO 3 − transporter, functioning as an Na + /HCO 3 − symporter, that has been shown to be upregulated in carbon limiting conditions in earlier studies (Shibata et al, 2002;Price, 2011). Our work had shown that overexpression of SbtA can promote the growth of PCC 7002 cells to the same levels as that observed with the overexpression of BicA (Gupta et al, 2020).…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…SbtA is a high-affinity, low flux, inducible sodium (Na +) dependent HCO 3 − transporter, functioning as an Na + /HCO 3 − symporter, that has been shown to be upregulated in carbon limiting conditions in earlier studies (Shibata et al, 2002;Price, 2011). Our work had shown that overexpression of SbtA can promote the growth of PCC 7002 cells to the same levels as that observed with the overexpression of BicA (Gupta et al, 2020).…”
Section: Introductionsupporting
confidence: 58%
“…RNA and proteins were extracted as in our earlier study (Gupta et al, 2020). For RNA isolation, 50 mL culture in exponential phase was centrifuged for 5 min at 4000 × g. The pellet was crushed in presence of liquid nitrogen using a pestle wiped with RNaseZAP and washed with RNase-free water.…”
Section: Analysis Of Gene Expression By Real-time Pcr and Western Blomentioning
confidence: 99%
See 2 more Smart Citations
“…PCC 7120 in response to CO 2 levels ( Figure 2 ). High CO 2 in light promotes a high rate of photosynthesis and the storage of photosynthate in the form of glycogen [ 13 , 109 , 110 , 111 ]. Strong expression of PEP synthase and PFOR under these conditions indicate glycolysis/gluconeogenesis through the metabolism of pyruvate, which is consumed in the TCA cycle to facilitate respiratory electron transport and to provide 2OG for amino acid synthesis (reviewed in [ 112 , 113 ]).…”
Section: Discussionmentioning
confidence: 99%